Peningkatan Pengetahuan Masyarakat tentang Pencegahan Penyakit Tidak Menular melalui Edukasi Keperawatan Komunitas - Winda Utari (Jurnal Pakar Pengabdian Kesehatan, 2026)
Non-communicable diseases (NCDs) such as hypertension, diabetes mellitus, heart disease, and stroke are major causes of morbidity and mortality in various countries, including Indonesia. One factor contributing to the high incidence of NCDs is the low public knowledge regarding risk factors and prevention efforts. Community nursing education is an effective promotive and preventive strategy to increase public understanding and encourage changes in healthy lifestyle behaviors. This community service activity aims to increase public knowledge about NCD prevention through community nursing education. The methods used included health education, interactive discussions, and distribution of educational media in the form of leaflets to participants. Evaluation was conducted using pre-test and post-test methods to measure changes in knowledge levels before and after the education activity. The results of the activity showed an increase in the average community knowledge score after the education. Participants also showed high enthusiasm during the discussion session and were able to re-explain various NCD risk factors, the importance of a healthy diet, physical activity, smoking cessation, and regular health check-ups. Community nursing education has proven effective in increasing public knowledge about NCD prevention and is expected to encourage the adoption of healthy lifestyle behaviors on an ongoing basis. Similar activities need to be carried out routinely by involving various stakeholders so that NCD prevention efforts can reach a wider community.